Happiness in action a philosopher's guide to the good life - Sandel, Adam Adatto (Harvard University Press, 2022)
Adam Sandel revives one of the oldest philosophical questions: What constitutes a good life? Drawing on thinkers ancient and modern, as well as his own experience as a record-setting athlete, he argues that fulfillment lies not in achieving goals but in forging a life journey that enables us to see our struggles and triumphs as an integrated whole.